Interaction of hepatitis C virus with the immune system in pregnant women with chronic hepatitis C - A. P. Tsibulkin; I. M. Khaertynova; G. F. Leonova; L. I. Maltseva (Акушерство, гинекология и репродукция, 2019)
Aim: to analyze the relation between hepatitis C virus (HCV) load, the immune reactivity, and the immune-mediated lesions in the liver during pregnancy in women with chronic hepatitis C (CHC). Materials and methods. The study included 1690 pregnant women, 107 of whom had IgG antibodies to HCV; in addition, 68 women (63.5 %) were diagnosed with chronic hepatitis C and had a positive test for HCV RNA. The diagnosis of CHC was confirmed by determining serum total anti-HCV IgG antibodies using an enzyme immunoassay. The qualitative and quantitative determination of HCV RNA in the blood was performed by polymerase chain reaction. The virus replicative activity was qualitatively assessed by the viral load: low - the level of HCV RNA was up to 103 lU/ml, moderate - from 103 to 106 lU/ml, and high - above 106 lU/ml. To quantify the results, we used the positivity index, i.e, the ratio of the serum optical density to the critical optical density (cut-off) in each test. Results. In the early stages of pregnancy, signs of severe immune-mediated hepatocyte injury persisted. In the II and Ill trimesters, there was an unusual discrepancy between the severity of viral load and the degree of hepatocyte injury as the course of CHC remained usual. Another evidence of the liver involvement in this immune-pathological mechanism was an 87 % decrease in alanine aminotransferase activity with an increase in the viral load in patients with CHC in the Ill trimester of pregnancy. Conclusion. Suppression of anti-HCV humoral immunity, but not cellular immunity, begins from early stages of pregnancy and is accompanied by a significant increase in hepatocyte lesions without an increase in the severity of the inflammatory process.